PENERAPAN PRINSIP HIGIENE SANITASI WARUNG MAKAN DI PASAR CIK PUAN PEKANBARU - Sari, Nila Puspita; Makomulamin, Makomulamin (PREPOTIF : JURNAL KESEHATAN MASYARAKAT, 2023)
Food is a source of energy and nutrients and can be a source of microorganisms and bacterial growth. Prevention of damage and diseases due to food done through the action of the application of sanitary higiene towards referring to Permenkes no. 1096 / menkes / per / vi / 2011, ranging from the food , food storage , food processing , equipment , food storage so and the presentation of food .This research aims to review the application of sanitary higiene food in Cik Puan’s Market Pekanbaru. The research is descriptive qualitative research .This research will be done at food stalls of Cik Puan’s Market Pekanbaru . The informants are 8 the stall owners eat the cik puan pekanbaru .Data collection by conducting interviews and observations .Research results in food stalls in the cik puan Pekanbaru , we can see that the raw food , processing food , Processing food , and the presentation of food in 8 food stalls in the cik puan pekanbaru sanitation food hygiene have met the requirements , while storage raw material, cooking utensils and eat , and food storage that is discovered yet qualified .It is hoped that the market operators can provide socialize higiene sanitation stall owners in the cik puan pekanbaru